Immersion in the visual arts and media - Liptay, Fabienne; Dogramaci, Burcu (Studies in intermediality, 2016)
pt. 1. Materials and sensations of immersion -- pt. 2. Archaeologies and technologies of immersion -- pt. 3. Landscapes and architectures of immersion